The impacts caused by digital radiology in Dentistry: A literature review (Research, Society and Development, 2023)
The aim of this study was to analyze and understand how digital radiographs are used in dental practice. There are advantages and disadvantages in using digital radiographs. The literature review was carried out with searches in the databases Pubmed, SCIELO, BVS, REVodonto and other scientific annals, using the keywords digital radiology, digitization, digital radiography and dentistry. The inclusion criteria were: articles in Portuguese and English, published between the years 2011 to 2022, in which 8 studies were included that address the aforementioned descriptors and excluded incomplete articles and abstracts, in this way the facts found were organized in chronological sequence (from 2012 to 2022) in a descriptive way for analysis of the studies. It is concluded that the handling of digital radiographs in dental routines provides some advantages, as well as for professionals as well as for patients, as it is a method that can be performed quickly and is suitable for reducing resources in terms of cost-effectiveness.